2016
DOI: 10.1016/j.gaceta.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Medida de la eficiencia de la atención primaria en Barcelona incorporando indicadores de calidad

Abstract: The results suggest the need to incorporate healthcare quality indicators as outputs when considering criteria for the streamlining of primary healthcare services. Failure to incorporate quality indicators is associated with various primary healthcare concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Quality standards are being increasingly used to analyze the functioning of different health care services, including primary care (Choi, 2016). In Catalonia, an autonomous region of Spain, two quality indicator systems are used to assess prescribing practices in relation to the appropriate use of drugs: the Pharmaceutical Prescription Quality Index (IQF) (Catalan Ministry of health, 2016), created in 1999, and the Pharmaceutical Prescription Quality Standard (EQPF) (Catalan Ministry of Health, 2017), created in 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Quality standards are being increasingly used to analyze the functioning of different health care services, including primary care (Choi, 2016). In Catalonia, an autonomous region of Spain, two quality indicator systems are used to assess prescribing practices in relation to the appropriate use of drugs: the Pharmaceutical Prescription Quality Index (IQF) (Catalan Ministry of health, 2016), created in 1999, and the Pharmaceutical Prescription Quality Standard (EQPF) (Catalan Ministry of Health, 2017), created in 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Filipe Amado and Dyson (2008) indicate that performance evaluation and improvement in primary health care should include structure, process, products, and results [25], that evaluation in primary care should be formative, involving the stakeholders if unintended consequences are to be avoided and performance is to be improved; and, in principle, DEA provides the basis for an appropriate methodology [26,27]. In this sense, Romano and Choi (2016) concluded that it is necessary to introduce quality indicators in the models [28].…”
Section: Introductionmentioning
confidence: 99%
“…Spain's healthcare system ranks third in the world, between 200 countries behind Hong Kong and Singapore in terms of efficiency (Vieira, 2018). To hold this position suggests that the Spanish Health System (hereinafter SHS), in particular, manages its resources under criteria of maximizing the quantity and quality of health (Romano & Choi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, these authors collect the use of output and input variables, as well as the units of analysis used. In relation to the HCC, they have been studied at a national level, among others by García-Latorre et al (1996) in Aragón (Zaragoza), Puig-Junoy (2000) in Aragón (Zaragoza), Huesca, Navarra and Cataluña, Cordero-Ferrera et al (2011) in Extremadura, Cordero-Ferrera et al (2016 in País Vasco, and Romano and Choi (2016) in Cataluña (Barcelona).…”
Section: Introductionmentioning
confidence: 99%